2015
DOI: 10.11648/j.sjph.20150302.24
|View full text |Cite
|
Sign up to set email alerts
|

Exclusive Breastfeeding up to Six Months is Very Rare in Tanzania: A Cohort Study of Infant Feeding Practices in Kilimanjaro Area

Abstract: Background: Exclusive breastfeeding (EBF) is recommended the first six months after birth as one of cost effective interventions in saving children's lives. Objective: To determine the prevalence of exclusive breastfeeding and describe the common foods introduced to infants before 6months. Design: A prospective cohort study. Setting: Poor community of Moshi urban, Kilimanjaro region, Tanzania. Subjects: Women in their third trimester and were followed to 18 months after delivery. A questionnaire was used to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
0
9
0
1
Order By: Relevance
“…The prevalence of early initiation of breastfeeding observed in the current study of 83% is higher than the proportions reported in earlier studies in Kilimanjaro region. Over time proportion of women initiating breastfeeding within an hour of birth increased from 70% in 2002-06 [30] to 77% in 2010-11 [31]. Tanzania Demographic and Health Survey of 2015-16 reported the national prevalence of early initiation of breastfeeding of 51%, with wide regional variations; ranging from 26% in Simiyu region to 80% in Tanga region.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of early initiation of breastfeeding observed in the current study of 83% is higher than the proportions reported in earlier studies in Kilimanjaro region. Over time proportion of women initiating breastfeeding within an hour of birth increased from 70% in 2002-06 [30] to 77% in 2010-11 [31]. Tanzania Demographic and Health Survey of 2015-16 reported the national prevalence of early initiation of breastfeeding of 51%, with wide regional variations; ranging from 26% in Simiyu region to 80% in Tanga region.…”
Section: Discussionmentioning
confidence: 99%
“…With regards to the area-specific issues around the study, there seems to be a slight improvement in EBF practices, when comparing the data from the present study with another study which was also done in Moshi, Tanzania. That study was based on cohort data collected in 2002 – 2006; EBF was measured using recall since birth at one, three and six months and the rates were 49%, 22% and 0.2% respectively 29. The improvement can be due to the counseling the mothers receive from health providers on the importance of EBF.…”
Section: Discussionmentioning
confidence: 99%
“…In a study from Tanzania, exclusive breastfeeding was rare, and solid foods seemed to be introduced before the age of 6 months, and semi solid foods was introduced already from 1 month’s age among some of the children [44]. In a recent study among seven West African countries, the introduction of complementary foods was commonly seen among children 3–5 months of age, and were further associated with diarrhea and acute respiratory infections [45].…”
Section: Discussionmentioning
confidence: 99%